Risk factors of bronchiolitis - I Gde Doddy Kurnia Indrawan; IB Subanada; Rina Triasih (Indonesian Pediatric Society Publishing House, 2013)
Background Bronchiolitis peak incidence is in children aged 2 -6 months. History of atopy in parents, non-exclusive breastfeeding, exposure to cigarette smoke, and infants living in crowded areas may be risk factors for bronchiolitis. Gestational of age at birth is also influences the mortality oflower respiratory tract infection. Objective To evaluate the following conditions as possible risk factors for bronchiolitis: history of atopy, non-exclusive breastfeeding, preterm infants, exposure to cigarette smoke, and 2:: 6 persons residing in the home. Methods A sex-matched case-control study was conducted by collecting data from medical records at Sanglah Hospital, Denpasar. The case group subjects met the diagnostic criteria for bronchiolitis and were aged 1-24 months. The control group included patients with diagnoses unrelated to the respiratory system. Data was analyzed using bivariate (Mc.N emar) and multivariate methods (logistic regression) with 95% confidence intervals and statistical significance value of P <0 .05. Results There were 96 subjects in our study, consisted of 48 subjects in the case group and 48 in the control group. The case and control groups were similar in baseline characteristics. The presence of history of atopy (OR 34.7; 95%CI 3 to 367, P=0.003), non-exclusive breastfeeding (OR 4.3; 95%CI 1.4 to 13, P=0.010), exposure to cigarette smoke (OR 3; 95%CI 1 to 9.2, P=0.047), and 2:: 6 persons living in the home (OR 7.9; 95%CI 2.6 to 24, P<0.0001) were found to be significant risk factors for bronchiolitis, while the preterm infants seem not significant as a risk factor of bronchiolitis (OR3; 95%CI 0.31 to 78.99, P=0.625). Conclusion History of atopy, non-exclusive breastfeeding, exposure to cigarette smoke, and 2:: 6 persons living in the home are found to be risk factors, while preterm infants seem not a risk factor for bronchiolitis.